FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING - Sulia, Sulia; Mie, Mie (Universitas Tanjungpura, 2025)
This study aims to determine the effect of Leverage, Liquidity, Firm Size, Firm Age and Activities on Financial Perfomance with Profit Management as intervening variable at Property and Real Estate companies listed in the Indonesia Stock Exchange for the 2018-2022 period. The population in this study was 86 companies using purposive sampling techniques and a research sample of 16 companies was obtained with a total of 80 companies observed. The data analysis method used is multiple linear regression analysis and path analysis using IBM SPSS Version 26. The results of the analysis show that simultaneously and partially the variabels Leverage, Liquidity, Firm Size, Firm Age and Activities have no effect on Profit Management. Simultaneously Levergae, Liquidity, Firm Size, Firm Age, Activities, Profit Management have effect on Financial Perfomance. Partially, Profit Management has a positive effect on Financial Perfomance. The Leverage and Liquidity variabels have a negative effect on Financial Perfomance, while the Firm Size, Firm Age and Activities variables have no effect on the Financial Perfomance of Property and Real Estate Companies listed in the Indonesia Stock Exchange for the 2018-2022 period. Profit Management is abe to intervene with the Leverage, Liquidity, and Firm Age variable on Financial Perfomance, while the Firm Size and Activities variables cannot be intervened by Profit Managament